THE PROBLEM OF WOMEN'S WRITING IN THE 20TH CENTURY: THE THREE FEMALE POETS OF "POESIA 61" - Cameira, Maria João (2018)
The purpose of this article is the recognition and appreciation of feminine writing in the twentieth century, focusing its attention on the three poets of Poesia 61:Fiama Hasse Pais Brandão, Maria Teresa Horta and Luiza Neto Jorge. The analysis of the common traits to these three languages - poetic reflexivity, intertextuality and eroticism - intends to show how these same aspects are treated in different ways, by differentiating them from each other and by distinguishing their poetic language. Referring to the literary background of feminine writing of the twentieth century, this study contributes to highlight the decisive importance of these three authors in the feminist poetry of the twentieth century.